A sketch of reality : the multigrade classroom in context of the reform of basic education and paintings in their steps fractals (2021)
ABSTRACT: The Mexican educational reform is based on transformations towards the conception of a new world, as a result of technological advances and new knowledge communities, where the parameters are established mainly by various international organizations, and where countries implement, evaluate, integrate and describe the necessary conditions for education. The multigrade classroom and the elements that are developed in it are conceptualized. The critical pedagogy of Gramsci and Freire should be part of the teaching preparation.